Linguistic construction of human trafficking in news reports on the Jeffrey Epstein case: A critical discourse analysis - Asmaa Amjad Alwan; Qasim Abbas Dhayef (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
The paper addresses the concept of human trafficking as a socially constructed problem, influenced by how news reports define exploitation, represent social actors, and convey patterns of control, responsibility, and power. Based on news coverage of the Jeffrey Epstein case, the study explores how human trafficking is linguistically constructed through lexical choices and discursive strategies, and how ideological meanings are framed in the selected data. The dataset consists of three news reports, with three extracts from each, selected for their relevance to human trafficking and their publication within the 2026 timeframe. The study employs a critical discourse analysis approach at two levels. At the micro level, it examines linguistic choices and discursive strategies, while at the macro level it analyzes ideological meanings, power relations, and framing practices in the reports. The findings at the micro level show that lexical choices and discursive strategies tend to represent victims as emotionally, legally, and coercively vulnerable, while institutions and elites are depicted through language emphasizing negligence, authority, or overwhelming power. At the macro level, the reports frame human trafficking as a structural problem sustained by institutional failure, bureaucratic shortcomings, and the influence of powerful actors, while also assigning responsibility and moral judgment. The study concludes that linguistic and ideological patterns are closely interconnected in constructing human trafficking in news discourse. Overall, the analysis demonstrates that trafficking is not portrayed as an isolated crime but as a phenomenon embedded in broader social and institutional structures, highlighting the role of media language in shaping public understanding of exploitation and its underlying conditions.